Herpes zoster-associated acute urinary retention in immunocompetent patient - Marques, Silvio Alencar [UNESP]; Hortense, Juliana (Soc Brasileira Dermatologia, 2014)
Herpes zoster-associated urinary retention is an uncommon event related to virus infection of the S2-S4 dermatome. The possible major reasons are ipsilateral hemicystitis, neuritis-induced or myelitis-associated virus infection. We report a case of a 65-year-old immunocompetent female patient who presented an acute urinary retention after four days under treatment with valacyclovir for gluteal herpes zoster. The patient had to use a vesical catheter, was treated with antibiotics and corticosteroids and fully recovered after eight weeks.
Keywords: Herpes Zoster; Treatment outcome; Urinary retention